2016
DOI: 10.1364/ao.55.003801
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical behavior of porphyrin functionalized nanodiamonds: an efficient material for optical power limiting

Abstract: The nonlinear optical mechanisms and the optical limiting behavior of porphyrin functionalized detonation nanodiamonds are investigated and compared to the conventional detonation nanodiamonds (DNDs). The optical limiting behavior is characterized by means of nonlinear transmittance, Z-scan, and scattered intensity measurements when submitted to a nanosecond pulsed Nd:YAG laser operating at the second harmonic wavelength. We found that the largest nonlinear attenuation was observed on the 4,4',4 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
3
14
2
Order By: Relevance
“…It is also two magnitudes higher than most guest–host optical limiting filters like the typical guest–host systems. Examples are PMMA samples doped with DND, carbon nanotubes, carbon nanohorns, or metal nanoparticles, which normally only achieve an attenuation around 10 −2 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also two magnitudes higher than most guest–host optical limiting filters like the typical guest–host systems. Examples are PMMA samples doped with DND, carbon nanotubes, carbon nanohorns, or metal nanoparticles, which normally only achieve an attenuation around 10 −2 …”
Section: Resultsmentioning
confidence: 99%
“…The most important involved mechanisms are nonlinear absorption, nonlinear refraction, and nonlinear scattering . Nonlinear refraction is the most significant mechanism in case of unfunctionalized detonation nanodiamonds (DNDs) . Nonlinear scattering dominates the optical limiting ability of most other nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…2 . The incident beam with a diameter of 7 mm is focused into the sample area through the lens L4, f4 = 200 mm in a f/30 focusing geometry 4 . The sample is placed on a motorized stage and is moved from −z to +z.…”
Section: Methodsmentioning
confidence: 99%
“…Among nanoparticles which are of great interest in the optical field, carbonaceous nanoparticles have demonstrated extremely interesting properties in order to develop nonlinear optical systems 1 , 2 . Moreover, previous studies showed that well controlled detonation nanodiamonds (DNDs) suspensions or functionalized DNDs could greatly improve the nonlinear properties of such material 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductors, 27 organic materials [28][29][30] and organic materials mixed with nanoparticles 31 are studied to improve optical limiting applications.…”
Section: Optical Limitingmentioning
confidence: 99%